PENGARUH PENERAPAN ASESMEN FORMATIF TERHADAP HASIL BELAJAR MATEMATIKA DI SD ISLAM AL AZKIYA DEPOK - Ami, Aminah; Hendro Prasetyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Formative assessment is an essential part of the learning process that provides continuous feedback to students to help them improve and enhance their learning outcomes. This study aims to determine the effect of implementing formative assessment on students’ mathematics learning outcomes at SD Islam Al Azkiya Depok. The research method used was a quantitative approach with a quasi-experimental design. The study population consisted of 60 fifth-grade students divided into two groups: an experimental class (30 students) that received structured learning with formative assessment, and a control class (30 students) that used conventional learning without continuous formative assessment. The research instruments included a mathematics learning achievement test and an observation sheet for the implementation of formative assessment. Data were analyzed using normality, homogeneity, and independent sample t-test to determine the differences in learning outcomes between the two groups. The results showed that the implementation of formative. Assessment had a significant effect on students’ mathematics learning outcomes, with the experimental class achieving an average score of 83.47, higher than the control class’s average of 76.20. The t-test results indicated that t_calculated (3.82) > t_table (2.00) at a significance level of 0.05, meaning that H₀ was rejected and H₁ was accepted. Thus, it can be concluded that the implementation of formative assessment has a positive and significant effect on improving students’ mathematics learning outcomes at SD Islam Al Azkiya Depok